Fatigue Capacity of Small Railway Concrete Bridges : Prevision of the Results of Swedish Full-scale Tests. Comparison and Analyses - Thun, Håkan; Ohlsson, Ulf; Elfgren, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2000)
In this report results and analyses are presented from a full-scale fatigue test on a typical Swedish railway concrete bridge. The tests were performed at Luleå University of Technology in 1996. The purpose of the test was to study static and fatigue behaviour of the bridge under increased load in order to check its remaining life length. The bridge was originally situated in Lautajokk about 200 km northwest of Luleå along the iron ore line between Luleå and Narvik in Norway. The bridge had a length of 6,1 m and a width of 4,1 m and had the shape of a trough. It was built in 1967 and had been in service for 20 years. In the tests, the bridge was exposed to 6 million load cycles between 50 and 360 kN. No failure occurred even though the Swedish Concrete code BBK 94 indicated that. Especially the connection between the slab and the longitudinal beams was in a critical state according to the code.A study regarding the fatigue shear capacity with the Swedish code and the present Eurocode EC2 (1991) has shown that the codes are conservative and that further studies are needed in this area.Methods are proposed that can be used to estimate the remaining life length (Strain/deflection criterion and Wöhler curves). An analysis using a fracture mechanics approach is presented as well as studies regarding concrete strength development for Swedish Railway concrete bridges.Measurements of deflections and strains have also been carried out on four railway bridges during passing of trains Godkänd; 2000; Bibliografisk uppgift: Final Report for an Investigation on Fatigue of Railway Concrete Bridges to ERRI D216, European Rail Research Institute; 20080611 (ysko)